Financial Ratios as Performance Measure: A Comparison of IFRS and Nigerian GAAP - Zayyad Abdul-Baki; Ahmad Bukola Uthman; Mubaraq Sanni (Journal of Accounting and Management Information Systems (JAMIS), 2014)
This study examines the effect of IFRS adoption on the performance evaluation of a case firm using some financial ratios selected from four major categories of financial ratios. The study was conducted through comparison of the ratios that were computed from IFRS based financial statements and Nigerian GAAP based financial statements. A One-Sample Kolmogorov-Smirnov Test was conducted to test for data normality. Mann-Whitney U test was employed in testing whether significant difference exists between the pair of ratios when the normality test showed a non-normal distribution of the data set. The result of the Mann-Whitney U test showed that there is no significant difference between the pair of ratios at 5% level of significance. It was concluded that the disclosure of IFRS compliant set of financial statements was not attributable to higher performance evaluation, through ratios, of the case firm. Rather, such disclosure could have been motivated by the capital needs theory or signaling theory.
Keywords: M41; 650; IFRS; financial ratios; Nigerian GAAP; capital needs theory; signaling theory